1998
DOI: 10.3109/10428199809058389
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P53 Predicts Treatment Failure in Aggressive Non-Hodgkin's Lymphomas

Abstract: Approximately 50% of patients with aggressive non-Hodgkin's lymphomas (NHL) achieve a complete remission (CR) and cure with combination chemotherapy. The International Index is a useful clinical measure that predicts the patients' tolerance of therapy and likelihood of achieving CR, but it is not a direct measure of chemosensitivity. In this study we have investigated the predictive value of the tumor suppressor gene, p53, as a biological marker for response to treatment in the aggressive NHL. A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…Overexpression of p53 protein is usually associated with a loss of p53 gene function [19], favoring drug resistance and a worse prognosis. Corroborating our results, Navaratnam et al [21]showed that patients with p53-positive tumors had a low rate of CR and a reduced overall survival. Abnormalities of p53 gene (mutation or overexpression) were associated with drug resistance and a shorter median PFS and OS (11.7 vs 21.5 months, p = 0.038) [16].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Overexpression of p53 protein is usually associated with a loss of p53 gene function [19], favoring drug resistance and a worse prognosis. Corroborating our results, Navaratnam et al [21]showed that patients with p53-positive tumors had a low rate of CR and a reduced overall survival. Abnormalities of p53 gene (mutation or overexpression) were associated with drug resistance and a shorter median PFS and OS (11.7 vs 21.5 months, p = 0.038) [16].…”
Section: Discussionsupporting
confidence: 62%
“…Overexpression of p53 is frequently associated with an abnormal protein function [19]and has a prognostic value [16, 20, 21, 22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…P53 protein expression differs with respect to histological subtypes in gastrointestinal lymphomas (17%-20%), whereas this rate ranges between 60% and 85% in high-grade lymphomas. Different studies have identified that P53 protein expression is an important prognostic factor that affects the treatment response and overall survival in patients with aggressive NHL (12,13). In our study, we found P53 expression in 61.5% of the patients with primary gastrointestinal DLBCL.…”
Section: Discussionsupporting
confidence: 57%
“…It has been suggested that the presence of p53 mutations influences the pathologic grade 10 but not the clinical behavior. Several studies showed a strong correlation between clinical progression and occurrence of p53 mutations, [11][12][13][14][15][16][17] but others did not. 18,19 Our aim was to establish the frequency and importance of abnormalities in p53 in SLVL.…”
Section: Introductionmentioning
confidence: 99%